Injury Characteristics and Outcomes of Patients With Inflammatory Bowel Disease After Trauma: A Propensity Score Matched Analysis. Issue 8 (21st October 2019) - Haac, Bryce E; Nemirovsky, Amy; Teeter, William; Geyer, Andrew; Birkett, Richard T; Cross, Raymond K; Engels, Michael; Stein, Deborah M; Bafford, Andrea C
Abstract: Background: The clinical course of patients with inflammatory bowel disease (IBD) after trauma is largely unknown. We sought to compare the clinical course of patients with IBD to those without. Methods: We conducted a retrospective case-control study of adult patients admitted to a level-1 trauma center from January 1, 2008, through October 1, 2015. Seventy-five patients with IBD were identified. Cases were matched to controls by age, sex, injury severity, and mechanism using 4:1 propensity score-matching analysis. Injury characteristics, clinical course, and infectious and noninfectious complications were compared using bivariate and multivariate analysis. Results: Participants had a mean age of 56 years and mean injury severity score of 15. Of the 75 cases, 44% had ulcerative colitis, 44% had Crohn's disease, and 12% had undetermined type. More cases were on an immunosuppressant (19% vs 2%, P < 0.01) or steroids (8% vs 2%, P = 0.02) on admission compared with controls. More cases had prior abdominal surgery ( P = 0.01). Cases had fewer brain injuries ( P = 0.02) and higher admission Glasgow Coma Scale ( P < 0.01) but required more neurosurgical intervention ( P = 0.03). Cases required more orthopedic surgeries ( P < 0.01) and more pain management consultations ( P = 0.04). In multivariable analysis, IBD was associated with increased odds of operative intervention, pain management consultation, venous thromboembolism, and longer hospital stay ( P < 0.05). Patients on immunosuppressants had increased odds of requiring surgery ( P = 0.04), particularly orthopedic surgery ( P < 0.01). Conclusions: Baseline factors associated with inflammatory bowel disease may place patients at higher risk for surgery and complications after trauma. Abstract : In this retrospective propensity-matched case-control study, we examined baseline characteristics, injury patterns, and clinical course of patients with IBD compared with controls after trauma. We found differences in baseline immunosuppressant and steroid use, surgical history, clinical course, and outcomes.